2014
DOI: 10.3109/07420528.2014.965315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine and imipramine in a model of acute rhythm disruption in BALB/c mice

Abstract: Circadian rhythm disturbances are among the risk factors for depression, but specific animal models are lacking. This study aimed to characterize the effects of acute rhythm disruption in mice and investigate the effects of imipramine and N-acetylcysteine (NAC) on rhythm disruption-induced changes. Mice were exposed to 12:12-hour followed by 10:10-hour light:dark cycles (LD); under the latter, mice were treated with saline, imipramine or NAC. Rhythms of rest/activity and temperature were assessed with actigrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Accordingly, NAC also reduced enhanced presynaptic excitatory neurotransmission to normal levels in the amygdala of valproate-exposed rats 68. NAC prevented rhythm disruption-induced anxiety in mice 69. The anxiolytic effects of NAC have also been documented in the light/dark model and in stress-induced anxiety behavior in zebrafish,70 as well as in the hole-board test, the light/dark model, the open field test, social interaction, and stress-induced hyperthermia in mice 71.…”
Section: Resultsmentioning
confidence: 90%
“…Accordingly, NAC also reduced enhanced presynaptic excitatory neurotransmission to normal levels in the amygdala of valproate-exposed rats 68. NAC prevented rhythm disruption-induced anxiety in mice 69. The anxiolytic effects of NAC have also been documented in the light/dark model and in stress-induced anxiety behavior in zebrafish,70 as well as in the hole-board test, the light/dark model, the open field test, social interaction, and stress-induced hyperthermia in mice 71.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, it was shown that the inhibition of the activity of nNOS/cGC/PKGII input pathway components [ 36 , 37 ] delayed the circadian phase, so we could hypothesize that the phase-delays induced by GSH or NAC could be generated by a redox-dependent inhibition of the same pathway, as occurs with NOS activity and L-arginine uptake by AS treatment in the retina [ 45 ]. While Wang et al [ 5 ] evidenced the effect of GSH on resting electrical activity in SCN slices, few circadian studies were done with NAC, which had inconsistent effects [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated NAC effects as an anxiolytic ( Mocelin et al, 2015 ; Santos et al, 2017 ) and antidepressant drug ( Magalhães et al, 2011 ; Berk et al, 2013 ; Costa-Campos et al, 2013 ; Pilz et al, 2015 ). Therefore, NAC has advantages over the existing therapies since, besides having a potential preventive effect, it may be able to treat the non-motor aspects of PD, which include depression, anxiety, cognitive impairment and sleep disturbances ( Klockgether, 2004 ).…”
Section: Discussionmentioning
confidence: 99%